Political marketing in the times of big data - Pawełczyk, Piotr; Jakubowski, Jakub (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
Academic considerations on the topic of political marketing very often boil down to discussing the political history of the 20th and 21st centuries, while failing to account for the significant changes in the range of instruments used to implement election strategies. However, the academic discussion about political marketing as an applied sub-discipline should take into account some mechanisms for accomplishing specified tasks. Therefore, the purpose of this paper is to fill this gap and try to examine the influence of the tools based on big data on the broad picture of what we name marketing activities in the field of politics. We would like to present readers with our hypothesis that the profound changes in this area that were particularly noticeable in the election and referendum campaigns in 2016 may provide a premise to identify a new paradigm in the discussion on the use of marketing strategies in political communication. It would be based on the Internet combining the function of a communication channel and a source of data about voters. This information is next used for marketing purposes. It should be emphasized that this mechanism that has been used in the field of commercial activities for almost a decade, in the field of politics produces completely new and potentially dangerous consequences for citizens.

Rozważania naukowe dotyczące marketingu politycznego bardzo często sprowadzają się do dyskusji na temat politycznej historii XX i XXI wieku z pominięciem istotnych zmian w zakresie narzędzi wykorzystywanych do realizacji strategii wyborczej. Tymczasem analiza naukowa dotycząca marketingu politycznego, jako subdyscypliny stosowanej, uwzględniać winna mechanizmy realizacji określonych zadań. Celem niniejszego artykułu jest więc uzupełnienie tej “luki” i próba zastanowienia się nad wpływem narzędzi opartych o Big data na szerszy obraz tego, co nazywamy zabiegami marketingowymi w obszarze polityki. Pragniemy też poddać pod osąd czytelnika hipotezę, iż daleko idące zmiany w tym obszarze, w szczególności widoczne w kampaniach wyborczych i referendalnych w 2016 r., mogą stanowić przesłankę wyodrębnienia nowego paradygmatu w dyskusji na temat wykorzystania strategii marketingowych w komunikowaniu politycznym. Jest on wynikiem połączenia funkcji kanału komunikacji (internet) z jednoczesnym wykorzystaniem go jako źródła zdobywania danych o wyborcach. Te są zaś wykorzystywane w celach marketingowych. Podkreślić należy, iż mechanizm ten, od niemal dekady stosowany w obszarze działań komercyjnych, na gruncie polityki rodzi zupełnie nowe, potencjalnie niebezpieczne dla obywatela konsekwencje.
Marketing polityczny w czasach big data
Keywords: political marketing; marketing polityczny; big data; big data; political communication; komunikowanie polityczne; political campaign; kampania wyborcza